Embracing Diversity: Implementing Inclusion-Based Islamic Education at SMALB Semarang to Meet Diverse Student Needs - Erry Nurdianzah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Learning for children with disabilities necessitates specialized approaches to ensure the attainment of educational objectives. However, the heterogeneity of students with special needs within a single educational institution presents unique challenges in addressing their diverse educational requirements. This study aims to explore inclusion-based Islamic education at SMALB Semarang. Employing a qualitative research methodology with a case study approach, data was collected through interviews with the school principal, three teachers, ten students, and ten student guardians. Observations focused on the learning process and the interaction between students and teachers, while documentation provided insights into school records. Data analysis involved categorizing, coding, and identifying themes relevant to the research topic. The findings revealed that students at SMALB Semarang were classified into two categories: C (mentally retarded) and D (physically impaired). The learning process was tailored to the needs of students, who were grouped into several classes based on criteria such as religion and type of disability. Addressing the diversity in Islamic education involved curriculum adjustments and the formation of specific study groups. The Islamic learning process utilized various tools, including embossed media, visual aids, and hearing devices. For students with type C disabilities, the Islamic education process frequently involved repetition of learning materials. Embracing student diversity based on disability type and religion is crucial for effectively conveying and ensuring the acceptance of Islamic teachings among the appropriate student groups.